A synthetic HIS4 regulatory element confers general amino acid control on the cytochrome c gene (CYC1) of yeast. - Hinnebusch, A G (1985)
Hybrid promoters constructed from upstream sequences of the yeast HIS4 promoter and the downstream element of the yeast CYC1 promoter place iso-1-cytochrome c (CYC1) expression under the general amino acid control, typical of HIS4. HIS4 fragments that confer regulation contain at least one copy of the sequence T-G-A-C-T-C that is repeated at HIS4 and other genes subject to the general control. A 14-base-pair synthetic oligonucleotide containing a single copy of the HIS4 repeat places CYC1 under the general control. Two copies of this oligonucleotide produce a derepressed level of expression nearly equivalent to that conferred by the largest HIS4 5' noncoding fragments we examined and direct regulated expression of a set of transcripts with 5' ends typical of the CYC1 promoter. Comparison of the expression levels conferred by the short synthetic repeat and larger HIS4 5' fragments reveals additional promoter elements required for maintaining efficient gene expression under repressing growth conditions.